The effects of preexercise caffeinated-coffee ingestion on endurance performance: An evidence-based review - Higgins, S.; Straight, C. R.; Lewis, R. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Endurance athletes commonly ingest caffeine as a means to enhance training intensity and competitive performance. A widely-used source of caffeine is coffee, however conflicting evidence exists regarding the efficacy of coffee in improving endurance performance. In this context, the aims of this evidence-based review were threefold: 1) to evaluate the effects of preexercise coffee on endurance performance, 2) to evaluate the effects of coffee on perceived exertion during endurance performance, and 3) to translate the research into usable information for athletes to make an informed decision regarding the intake of caffeine via coffee as a potential ergogenic aid. Searches of three major databases were performed using terms caffeine and coffee, or coffee-caffeine, and endurance, or aerobic. Included studies (n = 9) evaluated the effects of caffeinated coffee on human subjects, provided the caffeine dose administered, administered caffeine = 45 min before testing, and included a measure of endurance performance (e.g., time trial). Significant improvements in endurance performance were observed in five of nine studies, which were on average 24.2% over controls for time to exhaustion trials, and 3.1% for time to completion trials. Three of six studies found that coffee reduced perceived exertion during performance measures significantly more than control conditions (p < .05). Based on the reviewed studies there is moderate evidence supporting the use of coffee as an ergogenic aid to improve performance in endurance cycling and running. Coffee providing 3-8.1 mg/kg (1.36-3.68 mg/lb) of caffeine may be used as a safe alternative to anhydrous caffeine to improve endurance performance.